Determinan Pembelian Impulsif pada E-Commerce Shopee di Masa Pandemi Covid-19 - Mufid Suryani; Nida Nusaibatul A; Panji Nurul H (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the effect of hedonic shopping motives and motivations on impulse purchases at e-commerce shopee during the covid 19 pandemic. The analytical method in this study uses primary and secondary data, the test stages carried out are: validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, coefficient of determination, partial t test, simultaneous F test. The data used in this study used a questionnaire instrument, and 100 respondents valid data. The sampling method in this study is probability sampling. The testing tool used is SPSS. The results showed that the motive variable did not have a positive effect on impulse buying, the hedonic shopping motivation variable also did not have a positive effect on impulsive buying. Meanwhile, hedonic shopping motives and motivations have a simultaneous effect on impulse buying.